African Pragmatic Spiritualism as Neo-Science: A Bergsonian/Whiteheadian Critique of Hountondji - Anthony Afe. Asekhauno; Emmanuel Asia (SIASAT, 2021)
Arguably, spiritualism is the most central of African philosophical systems. Amongst Africans, all reality is replete with spiritual involvement a pragmatic involvement. Spiritualism is typical and topical all around traditional African cultures, empirically manifested in all areas of human knowledge and experience including medicine, communication and transportation, entertainment, and the disquisition of justice. African spiritual capacity is a pragmatic reflection of African didactic strides. While this categorization may be apt and adequate for those sympathetic with truth and the African course, it, however, is either untrue or unscientific, a mark of primitivism. Clearly, it is outmoded and untenable to some others, including the Ivoirian-born Beninese Paulin Hountondji. This work reviews the major substance of Hountondji’s critical views on African spiritualism with a view to debunking them by adducing by the canons set by the process philosophies of Henry Bergson and Alfred North Whitehead. The trajectory attempts to build a theoretical pedestal for the grounding of an African esoteric philosophy, which is at once uniquely spiritual and pragmatic—hence the phrase, pragmatic spiritualism or spiritual pragmatism; a method and model recommended for wider feat in all human affairs and dealings with nature.